2009
DOI: 10.1016/j.virol.2009.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Small effective population sizes and rare nonsynonymous variants in potyviruses

Abstract: Analysis of nucleotide sequence polymorphism in complete genomes of 12 species of potyviruses (single-stranded, positive-sense RNA viruses, family Potyviridae) revealed evidence that long-term effective population sizes of these viruses are on the order of 104. Comparison of nucleotide diversity in non-coding regions and at synonymous and nonsynonymous sites in coding regions showed that purifying selection has acted to eliminate numerous deleterious mutations both at nonsynonymous sites and in non-coding regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…However, especially at the initial locale, it may have emerged on more than one occasion and followed more than one genetic trajectory, as found in recent well-sampled animal virus emergences (e.g. [32]); competition between emerging virus populations for a limited host population [33 ] probably selected among them.…”
Section: Discussionmentioning
confidence: 99%
“…However, especially at the initial locale, it may have emerged on more than one occasion and followed more than one genetic trajectory, as found in recent well-sampled animal virus emergences (e.g. [32]); competition between emerging virus populations for a limited host population [33 ] probably selected among them.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported PGIM patterns consistent with slightly deleterious amino acid changes. Excess rare polymorphisms and higher r pd for nonsynonymous compared to synonymous variation appear to be general patterns in viral (Edwards et al 2006;Pybus et al 2006;Hughes 2009) and bacterial genomes (Hughes 2005;Charlesworth and Eyre-Walker 2006;Rocha et al 2006;Hughes et al 2008) as well as in animal mtDNA (Ballard and Kreitman 1994;Nachman et al 1996;Rand and Kann 1996;Hasegawa et al 1998;Wise et al 1998;Weinreich and Rand 2000;Gerber et al 2001;Subramanian et al 2009). Similar patterns have been noted in nuclear genes from yeast (Doniger et al 2008;Liti et al 2009), Drosophila (Akashi 1996;Fay et al 2002;Loewe et al 2006;Andolfatto et al 2011), humans (Cargill et al 1999;Sunyaev et al 2000;Hughes et al 2003;Williamson et al 2005;Boyko et al 2008;Keightley and Halligan 2011;Subramanian 2012), mice (Halligan et al 2010), and plants (Bustamante et al 2002;Nordborg et al 2005;Foxe et al 2008;Fujimoto et al 2008;Gossmann et al 2010;Branca et al 2011;.…”
Section: Within-lineage Contrasts Of Polymorphism and Divergencementioning
confidence: 99%
“…A large fraction (~70 %) of point substitutions are deleterious or lethal (Carrasco et al, 2007;Sanjuan et al, 2004) meaning that most mutations in RNA genomes are not likely to survive, particularly the non-synonymous changes (Hughes, 2009). Similar effects have been reported for animal viruses (Pybus et al, 2007).…”
Section: Long-term Rates -Macroevolutionmentioning
confidence: 99%
“…A recent analysis (Hughes, 2009) of the population genetics of a large sample of complete potyvirus genomes has found that their effective populations are in the order of 10 4 . This, and the birth-death topology, suggest that despite large populations within individual infected plants, only small numbers survive the hazards of being transmitted to new hosts; there is probably strong selection for survival of the ecologically fittest.…”
Section: Long-term Rates -Macroevolutionmentioning
confidence: 99%